2018
DOI: 10.1016/j.ijintrel.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Hype or hope? A new look at the research on cultural intelligence

Abstract: Cultural intelligence (CQ), the capability by which expatriates, managers, and others involved in cross-cultural interactions function effectively in a globalized world, was introduced in 2003 and has garnered wide attention recently. In this paper, we present a detailed and up-to-date review of 142 empirical articles in the CQ research field. We first examine the concept of CQ, including its definition, structure, measurement, and validity. We then review the vast number of empirical studies that investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 170 publications
2
98
1
3
Order By: Relevance
“…In addition to the part shown in Figure 2 above, you should pay attention to the source when learning phrases. For example, many phrases in English come from the Bible, with a strong religious culture [4] .…”
Section: Figure 2 Application Statistics Of "Internet +" In Translatimentioning
confidence: 99%
“…In addition to the part shown in Figure 2 above, you should pay attention to the source when learning phrases. For example, many phrases in English come from the Bible, with a strong religious culture [4] .…”
Section: Figure 2 Application Statistics Of "Internet +" In Translatimentioning
confidence: 99%
“…This construct represents the capacity to effectively adapt to contexts with a strong cultural component, and it could be considered a protective factor against radicalization and violent extremism (Fang et al, 2018; Trujillo and Moyano, 2018). Although it is a territory that still needs to be explored, Moyano et al (2015) found that cultural intelligence showed a negative relationship with constructs such as the meaning of life and the need for cognitive closure, which, in turn, have been proposed as factors influencing violent extremism (Klein and Kruglanski, 2013; Kruglanski et al, 2015; Trujillo et al, 2016).…”
Section: The Role Of Identity and Culturementioning
confidence: 99%
“…Empirical research shows that it reliably predicts outcomes such as global leadership (e.g., Sutton et al, 2013), negotiation performance (e.g., Imai and Gelfand, 2010), expatriation intention (e.g., Richter et al, 2019) (forthcoming), and job performance (e.g., Ang et al, 2007). Furthermore, a number of journals have published special issues on CQ (e.g., Chiu et al, 2013), and there are already several review articles on the concept (e.g., Ott and Michailova, 2018;Fang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Review studies address the definition of CQ in contrast to the more traditional international business terminology (e.g., Andresen and Bergdolt, 2017;Levy et al, 2007;Johnson et al, 2006). Moreover, the authors have reviewed the literature with a focus on structuring (empirical) studies based on CQ (Fang et al, 2018;Ott and Michailova, 2018). Ott and Michailova (2018) presented an overview of studies that refer to the concept as an antecedent, moderator, or mediator in relation to different outcomes, such as leadership, performance, and effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation